1992
DOI: 10.1113/jphysiol.1992.sp019324
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms of transient inward current in the absence of Na(+)‐Ca2+ exchange in rabbit cardiac Purkinje fibres.

Abstract: was shifted to -12-5 and + 5 mV, respectively. The peak outward TI was also greatly suppressed when [Cl-]0 was decreased. The magnitude of peak inward TI was not significantly different with either choline chloride or sucrose substitution.7. Two anion transporter blockers, 4,4'-diisothiocyanatostilbene-2,2'disulphonic acid (DIDS) and 4-acetamide-4'-isothiocyanatostilbene-2,2'-disulphonic acid (SITS), which are known to block the Cl-conductance in cardiac tissues, abolished outward TI at a concentration of 10 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Therefore, direct comparison with our results remains difficult. Our results are, however, consistent with the observation by Han & Ferrier (1992) …”
Section: Voltage Clamp and [Ca2+]i Measurementssupporting
confidence: 49%
See 1 more Smart Citation
“…Therefore, direct comparison with our results remains difficult. Our results are, however, consistent with the observation by Han & Ferrier (1992) …”
Section: Voltage Clamp and [Ca2+]i Measurementssupporting
confidence: 49%
“…However, large and slow [Ca2+]i-dependent currents were recently described during [Ca2+]i overload in multicellular Purkinje fibres studied with dual microelectrode voltage clamp (Han & Ferrier, 1992). In this preparation, outward currents and a small fraction of the inward currents were ascribed to Cl-currents.…”
Section: Voltage Clamp and [Ca2+]i Measurementsmentioning
confidence: 99%
“…Since then the calcium ion dependence of this Cl-component has been documented by several authors (e.g. Zygmunt & Gibbons, 1991;Sipido, Callewaeert & Carmeliet, 1993) (Mechmann & Pott, 1977) and chick embryonic heart cells (Clusin, 1983;Clusin, Fischmeister & DeHaan, 1983) to caffeine also elevated the myoplasmic calcium ion concentration ([Ca2+] (Kass, Tsien & Weingart, 1978b;Colquhoun, Neher, Reuter & Stevens, 1981;Cannell & Lederer, 1986;Ehara, Noma & Ono, 1988;Han & Ferrier, 1992) or (2) a [Ca2+]1-modulated, electrogenic Na'-Ca2+ exchanger ; Arlock & Katzung, 1985;Beuckelmann & Wier, 1989). More recently, however, the involvement of Icl(ca) in ITI generation (Zygmunt, 1994;Papp, Sipido, Callewaert & Carmeliet, 1995;Laflamme & Becker, 1996;Collier, Levesque, Kenyon & Hume, 1996) has been suggested.…”
Section: Introductionmentioning
confidence: 86%
“…Non-selective cation currents have been described mainly in single channel experiments (Ehara et al 1988) but they have also been demonstrated in multicellular preparations (Cannel & Lederer, 1986;Han & Ferrier, 1992), where direct control of the composition of intra-and extracellular spaces was difficult. In the present study, where such technical limitations are less likely to be encountered, we were unable to demonstrate the activation of a non-specific cationic membrane conductance.…”
Section: Cell Isolationmentioning
confidence: 99%
See 1 more Smart Citation